Applied of Statistics to Building Entrepreneurship Intention Through Self Efficacy, Adversity Quotient, and Need for Achievement In Students of The Faculty of Economics and Business, Labuhanbatu University - Andri Yusuf; Rizki Syahputra; Junita Lubis (JINAV: Journal of Information and Visualization, 2022)
The purpose of this study is to find out the true picture of self-efficiency, adversity quotient and need for achievement in building entrepreneurial intentions in students. Collecting data in this study through research with a type of quantitative research in the form of distributing questionnaires. This research uses descriptive analysis, classical assumption test, multiple linear regression test and partial test. Respondents in this study were 65 students of the Faculty of Economics and Business, Labuhanbatu University. The results of this study state that self-efficacy, adversity quotient and need for achievement have a positive and significant effect on building entrepreneurial intentions in students of the Faculty of Economics and Business, Labuhanbatu University. The coefficient of determination obtained is 0.678, it indicates that self-efficacy, adversity quotient and need for achievement owned by students of the Faculty of Economics and Business, Labuhanbatu University, have presented a contribution of 67.8% in building entrepreneurial intentions. The remaining 32.2% was used as a contribution from outside this study which was not examined by researchers.